2015
DOI: 10.1186/s12974-015-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

Active immunization against complement factor C5a: a new therapeutic approach for Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is the most common neurodegenerative disease characterized by neuronal loss due to amyloid beta aggregations, neurofibrillary tangles, and prominent neuroinflammation. Recently, interference with neuroinflammation as a new therapeutic approach for AD treatment gained great interest. Microglia cells, one of the major contributors in neuroinflammation, are activated in response to misfolded proteins such as amyloid β and cell debris leading to a sustained release of pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…Fonseca et al demonstrated that the treatment with an antagonist of C5aR (PMX205) resulted in a reduction of pathological markers and improved memory skills in two different mouse models of AD [36]. In our previous study we showed that immunization against the proinflammatory complement factor C5a by AFF1 vaccine is able to interfere with microglia activation and thus neuropathology in Tg2576 mice, a model of AD [37]. AFF1 treated mice did not only show a reduced number of activated microglia in the hippocampal region, but also improved contextual learning and memory skills [37].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Fonseca et al demonstrated that the treatment with an antagonist of C5aR (PMX205) resulted in a reduction of pathological markers and improved memory skills in two different mouse models of AD [36]. In our previous study we showed that immunization against the proinflammatory complement factor C5a by AFF1 vaccine is able to interfere with microglia activation and thus neuropathology in Tg2576 mice, a model of AD [37]. AFF1 treated mice did not only show a reduced number of activated microglia in the hippocampal region, but also improved contextual learning and memory skills [37].…”
Section: Introductionmentioning
confidence: 88%
“…The proprietary AFFITOME ® technology [39] was used to develop short immunogenic peptides (AFFITOPE ® s), which mimic either the C-terminal epitope of murine C5a [37] or the N-terminal epitope of human Aβ [13]. Vaccines were prepared as described previously [37].…”
Section: Vaccine Preparation and Immunization Schemementioning
confidence: 99%
See 3 more Smart Citations